2017
DOI: 10.1007/s10071-017-1097-3
|View full text |Cite
|
Sign up to set email alerts
|

Practice makes perfect: familiarity of task determines success in solvable tasks for free-ranging dogs (Canis lupus familiaris)

Abstract: Domestic dogs' (Canis lupus familiaris) socio-cognitive faculties have made them highly sensitive to human social cues. While dogs often excel at understanding human communicative gestures, they perform comparatively poorly in problem-solving and physical reasoning tasks. This difference in their behaviour could be due to the lifestyle and intense socialization, where problem solving and physical cognition are less important than social cognition. Free-ranging dogs live in human-dominated environments, not und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Our study revealed that free-ranging dog groups performed better in the familiar task (Task 2) as compared to the unfamiliar one (Task 1) when faced with tasks with single food rewards. This was consistent with the earlier findings with individual free-ranging dogs and further substantiates dogs’ inferior abilities in physical cognitive task solving situations like string pulling (Osthaus et al 2005; Bhattacharjee et al 2017a). Dogs also showed a much faster reaction to Task 2 than Task 1, emphasizing the role of familiarity (Bhattacharjee et al 2017a).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our study revealed that free-ranging dog groups performed better in the familiar task (Task 2) as compared to the unfamiliar one (Task 1) when faced with tasks with single food rewards. This was consistent with the earlier findings with individual free-ranging dogs and further substantiates dogs’ inferior abilities in physical cognitive task solving situations like string pulling (Osthaus et al 2005; Bhattacharjee et al 2017a). Dogs also showed a much faster reaction to Task 2 than Task 1, emphasizing the role of familiarity (Bhattacharjee et al 2017a).…”
Section: Discussionsupporting
confidence: 91%
“…Task 1 had earlier been shown to be solved by individual free-ranging dogs, suggesting no physical limitation on part of the dogs. However, a small success rate could be addressed by ‘task difficulty’ along with unfamiliarity, also, Task 2 was highly familiar for these dogs from a scavenging perspective and solved at a higher rate compared to Task 1 (Bhattacharjee et al 2017a). In order to eliminate any anthropomorphic bias, we have emphasized the familiarity of the tasks (Task 1 and 2), rather than their difficulty levels.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations